2021
DOI: 10.2478/bhk-2022-0002
|View full text |Cite
|
Sign up to set email alerts
|

Do the body weight perception and body mass index affect the participation of exercise?

Abstract: Study aim: In this study, it is aimed to find out the exercise preferences based on the Body Mass Index (BMI) and Body Weight Perception (BWP), and to determine the consistency between BMI and BWP calculated via the self-reporting method. Material and methods: The study was conducted total of 297 volunteers, included 174 females (Mage = 27.19 ± 9.94 years) and 123 males (Mage = 26.08 ± 10.15 years), who were members of the physical activity center. The height and body weight v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition, studies on self-weight perception also found that perceived overweight or obesity may lead to numerous unhealthy conditions and are associated with future weight gain ( 22 , 38 , 39 ). An obesity self-weight perception may cause obesity anxiety, which is associated with obesity and may increase individual stress, leading to future eating and physiological disorders ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies on self-weight perception also found that perceived overweight or obesity may lead to numerous unhealthy conditions and are associated with future weight gain ( 22 , 38 , 39 ). An obesity self-weight perception may cause obesity anxiety, which is associated with obesity and may increase individual stress, leading to future eating and physiological disorders ( 40 ).…”
Section: Discussionmentioning
confidence: 99%